STEM and the creative and cultural industries: the factors keeping engineers from careers in the CCIs - Turegeldinova, Aliya; Amralinova, Bakytzhan; Fodor, Máté Miklós; Rakhmetullina, Saule; Konurbayeva, Zhadyra; Kiizbayeva, Zhadyra (Frontiers in Communication, 2024)
Engineers in the Creative and Cultural Industries (CCIs) are underrepresented, despite high demand for their expertise resulting from digitalization. Increasing the quantity of engineers in CCIs has emerged as a policy goal, since experiments have shown that combining engineering and creative abilities enhances productivity and innovation output. It is therefore unsurprising that the high and unmet demand for engineers in CCIs is well documented. However, the factors contributing to them not taking up jobs in these sectors are not well understood. The existing knowledge mostly comes from the analysis of deficiencies within the CCIs, including cultural disparities, skill profiles and economic factors. But why engineers themselves consider CCIs to provide inappropriate career tracks is little understood. The present study aims to bridge this knowledge gap through two main pillars. First, it develops a novel theoretical framework that aims to provide a taxonomy operationalizing the reasons for which engineers do not engage with the CCIs. This framework categorizes the social and economic barriers that keep engineers from pursuing careers in the CCIs. It includes economic factors, educational path dependencies, integration and interest. Second, our study offers preliminary quantitative insights into how the framework operates in practice, identifying key barriers without drawing definitive classifications. This analysis serves to highlight patterns and considerations for the future. The data source used is a survey among 104 university engineering and STEM students. Our results indicate that economic factors, such as poor salaries and job instability that are both prevalent in the CCIs are not the major barriers keeping engineers from the CCIs. They do not feel that educational investment would bear insufficient return. Instead, they feel ill-equipped to integrate into CCIs because of perceived deficiencies in artistic abilities. Furthermore, educational path dependencies for engineers do not necessarily support multidisciplinary education or counseling toward careers in the CCIs. These further exacerbate their worries regarding integration in the CCIs. These issues identified by our exploratory study can be resolved, predominantly because engineering students demonstrate inherent interest in arts and culture. Our research identifies the need for implementing specific changes to promote education and career guidance that span several disciplines.